Interaction of tetraspan(in) TM4SF5 with CD44 promotes self‐renewal and circulating capacities of hepatocarcinoma cells. Issue 6 (18th March 2015) - Lee, Doohyung; Na, Juri; Ryu, Jihye; Kim, Hye‐Jin; Nam, Seo Hee; Kang, Minkyung; Jung, Jae Woo; Lee, Mi‐Sook; Song, Haeng Eun; Choi, Jungeun; Lee, Gyu‐Ho; Kim, Tai Young; et al.
<x xml:space="preserve">Abstract</x> Tumor metastasis involves circulating and tumor‐initiating capacities of metastatic cancer cells. Epithelial‐mesenchymal transition (EMT) is related to self‐renewal capacity and circulating tumor cell (CTC) characteristics for tumor metastasis. Although tumor metastasis is a life‐threatening, complicated process that occurs through circulation of tumor cells, mechanistic aspects of self‐renewal and circulating capacities have been largely unknown. Hepatic transmembrane 4 L six family member 5 (TM4SF5) promotes EMT for malignant growth and migration, so it was rationalized that TM4SF5, as a hepatocellular carcinoma (HCC) biomarker, might be important for metastatic potential. Here, self‐renewal capacity by TM4SF5 was mechanistically explored using hepatocarcinoma cells with or without TM4SF5 expression, and we explored whether they became CTCs using mouse liver‐orthotopic model systems. We found that TM4SF5‐dependent sphere growth correlated with CD24−, aldehyde dehydrogenase (ALDH) activity, as well as a physical association between CD44 and TM4SF5. Interaction between TM4SF5 and CD44 was through their extracellular domains with N‐glycosylation modifications. TM4SF5/CD44 interaction activated proto‐oncogene tyrosine‐protein kinase Src (c‐Src)/signal transducer and activator of transcription 3 (STAT3)/Twist‐related protein 1 (Twist1)/B‐cell‐specific Moloney murine leukemia virus integration site 1 (Bmi1) signaling for spheroid formation, whereas disturbing the interaction, expression, or activity of any component in this signaling pathway inhibited spheroid formation. In serial xenografts using 200∼5, 000 cells per injection, TM4SF5‐positive tumors exhibited subpopulations with locally increased CD44 expressions, supporting for tumor cell differentiation. TM4SF5‐positive, but not TM4SF5‐ or CD44‐knocked‐down, cells were identified circulating in blood 4‐6 weeks after orthotopic liver injection using in vivo laser scanning endomicroscopy. Anti‐TM4SF5 reagent blocked their metastasis to distal intestinal organs. Conclusion: TM4SF5 promotes self‐renewal and CTC properties supported by TM4SF5+/CD44+(TM4SF5‐bound)/ALDH+/CD24− markers during HCC metastasis. (Hepatology 2015;61:1978‐1997)